Stimulating Impulse Buying of Cosmetics and Skincare Products in Live Commerce: The Role of Streamer Attractiveness, Interactivity, and Expertise on TikTok Indonesia - Eunha Kim; Dewi Tamara (Eduvest - Journal of Universal Studies, 2026)
Live commerce, which combines the advantages of offline and online shopping, is gaining attention as an effective sales channel in Indonesia's rapidly growing e-commerce market. In particular, TikTok Shop integrates social media and live commerce, allowing sellers to leverage live streamers' interactions with viewers to stimulate real-time purchases. This research examines how live streamers' attributes — such as attractiveness, interactivity, and expertise — influence impulsive buying through hedonic and utilitarian values within the Stimulus–Organism–Response (S-O-R) framework. This research adopts a quantitative approach and focuses on individuals in Indonesia who have watched cosmetics and skincare live streaming on TikTok Shop. Data from 342 valid responses were collected in February 2026 through an online questionnaire distributed via Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that streamer attractiveness and interactivity significantly increase consumers' hedonic value, which in turn strongly drives impulsive buying, whereas utilitarian value does not have a significant effect. The findings suggest that in TikTok live commerce, where shopping is closely integrated with entertainment and social interaction, emotional enjoyment rather than functional evaluation becomes the primary driver of impulsive purchases. Future studies should use more diverse samples, target first-time buyers, compare different streamer types, and incorporate factors such as brand trust to better understand how streamer attributes influence impulsive buying across different contexts.